Posterior only instrumentation without fusion in thoracolumbar burst fractures - Dev Sharma, Bishnu; Prasad Regmi, Ananda; Prakash Dawadi, Tej; Acharya, Devendra (Journal of Chitwan Medical College, 2025)
Introduction: Thoracolumbar fractures are the most common vertebral injury. Burst fractures in this transition zone are often unstable, requiring surgery. Short-segment posterior instrumentation without fusion is preferred treatment to preserve spinal motion, but it can have complications like implant failure and increased kyphosis. This study aims to evaluate the outcome of short-segment fixation without fusion in thoracolumbar burst fractures. Method: This was a prospective study conducted at Chitwan Medical College from Oct 2022 to Mar 2024. Ethical approval was obtained. Thoracolumbar burst fractures treated with short-segment pedicle screw fixation one-one level above and below, without fusion and with one-year follow-up, were included. Multi-level spinal injuries, osteoporotic/metastatic fractures and polytrauma were excluded. Visual Analogue Scale (VAS), Smiley-Webster Scale (SWS), and radiological anterior body height ratio and kyphotic angle were analysed. The IBM SPSS-16 was used for analysis, means were compared using a paired-samples t-test, at CI 95% and p<0.05 was considered statistically significant. Result: There were 45 patients with thoracolumbar burst fractures, 18(40%) AO A3 and 27(60%) AO A4 fractures, mean age of 45.38±15.68 years, 29(64.44%) males and 16(35.56%) females, fall from height 30(66.67%), and L1 fractures 18(40%). All fractures united with 22(48.89%) excellent and 16(35.56%) good results on SWS. Anterior body height ratio improved by 0.42±0.11 and kyphotic angle by 18.810±4.520 (p<0.001). The VAS improved significantly from 4.87±1.11 at discharge to 0.82±0.94 at final follow-up (p<0.001). The overall complication rate was 6(13.33%). Conclusion: Short-segment posterior instrumentation without fusion provides satisfactory results for surgically treated thoracolumbar burst fractures.